Studi Kajian Air Baku Spam Tembudan - Tambaru Tambaru (Pusat riset dan Inovasi Nasional, 2025)
The Drinking Water Supply System (SPAM) is essential infrastructure for ensuring access to clean water. SPAM Tembudan, located in Batu Putih District, Berau Regency, plays a key role in supplying raw water for both domestic and non-domestic uses. This study analyzes the sustainability of SPAM Tembudan by evaluating raw water quality, availability, and system efficiency. Primary data were collected through field surveys, water sampling, and interviews with operators and residents. Water quality was assessed based on physical, chemical, and biological parameters, following Ministry of Health Regulation No. 492/Menkes/Per/IV/2010. Availability was evaluated through flow rate measurements and community water demand, while system efficiency was assessed by examining treatment efficiency and water loss (Non-Revenue Water/NRW). Findings reveal that most water quality parameters meet national standards, though some show signs of potential contamination. In terms of availability, raw water is currently sufficient to meet demand, but seasonal changes particularly during the dry season threaten long-term sustainability. The analysis also identifies inefficiencies in the distribution network, with notable water losses that need addressing. To ensure the long-term sustainability of SPAM Tembudan, the study recommends enhancing the treatment process, improving raw water resource management, and reducing distribution losses. Encouraging community involvement and strengthening the capacity of local operators are also critical for maintaining the system’s performance. These strategies aim to secure reliable, high-quality drinking water for the community while supporting sustainable resource use.